THE IMPORTANCE OF VOCABULARY IN THE CLASSROOM AND SUGGESTIONS FOR THE EFFECTIVE WAY OF ENGLISH VOCABULARY TEACHING IN ELT - Usein, Arafat (International Scientific Journal Vision, 2023)
Vocabulary is a crucial component in language learning and of critical importance to the typical language learner. If the student lacks the vocabulary, he will be unsuccessful to function in any particular communication. Of course, we do not insist that the vocabulary is the whole story. Also the grammar or structure of a language is important. The need to teach system of the language is obvious, as grammatical knowledge allows us to generate sentences. However, we must have words that we wish to express ourselves in any particular. Unfortunately the importance of vocabulary teaching and learning in EFL has been neglected. Teachers assume that their students will learn words incidentally. It is thought that the vocabulary expansion will happen through the practice of other language skills. Therefore, teachers need to balance vocabulary teaching with grammar and other language skills so they will make sure that they are not neglecting any aspect of language learning. Teachers need to be aware of and expand vocabulary teaching techniques. This article deals with some of the ways the vocabulary is taught at schools. It also provides with some of the favorable vocabulary teaching activities and techniques for the students of English Language. Some teachers give their native language translation of the new words when teaching vocabulary. But there are teachers who use a variety of techniques to communicate meaning of new words without recourse to the native language. The best way of developing any learner’s vocabulary acquisition is to help the students encounter it in situations and contexts which are as authentic as possible, without causing the learners to be overwhelmed and frustrated by the quantity and difficulty of the new material. This study will be carried out with questionnaire administered to 20 English language teachers who have been teaching at different high schools in North Macedonia. Techniques used by teachers should provide creative ways for students to use the new vocabulary in meaningful and interesting context. So the purpose of vocabulary teaching techniques will be to develop the learner’s command of target language vocabulary.